2017
DOI: 10.1016/j.ajpath.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Monocyte Chemotactic Protein-1 Inhibition Modifies Renal Macrophages and Restores Glomerular Endothelial Glycocalyx and Barrier Function in Diabetic Nephropathy

Abstract: Inhibition of monocyte chemotactic protein-1 (MCP-1) with the Spiegelmer emapticap pegol (NOX-E36) shows long-lasting albuminuria-reducing effects in diabetic nephropathy. MCP-1 regulates inflammatory cell recruitment and differentiation of macrophages. Because the endothelial glycocalyx is also reduced in diabetic nephropathy, we hypothesized that MCP-1 inhibition restores glomerular barrier function through influencing macrophage cathepsin L secretion, thus reducing activation of the glycocalyx-degrading enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 38 publications
2
59
1
Order By: Relevance
“…Furthermore, proinflammatory activation and CCR2 have been implicated in acute and chronic kidney disease (9,40,41) and cardiovascular disease (6,42,43), underlining the relevance of our findings for kidney and cardiovascular patients. Patients with chronic kidney disease show increased arterial inflammation and increased proinflammatory phenotype of monocytes, as displayed by increased CCR7 and CCR2 expression (9).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, proinflammatory activation and CCR2 have been implicated in acute and chronic kidney disease (9,40,41) and cardiovascular disease (6,42,43), underlining the relevance of our findings for kidney and cardiovascular patients. Patients with chronic kidney disease show increased arterial inflammation and increased proinflammatory phenotype of monocytes, as displayed by increased CCR7 and CCR2 expression (9).…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, the observed correlation between the number of interstitial CD68+ macrophages and renal function indicated that macrophages play a role in DN progression 66. Since it is known that MCP‐1 can regulate recruitment of macrophages, a recent study by Boels et al 67. examined the effect of inhibiting MCP‐1 in diabetic mice.…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%
“…MCP‐1 inhibition with Spiegelmer emapticap pegol (NOX‐E36) in diabetic mice resulted in reduced CCR2 expression in circulating monocytes and a reduction in albuminuria, the albumin‐to‐creatinine ratio (ACR) and inflammation without changing the overall number of macrophages in the kidney. Instead, it was observed that diabetic mice receiving NOX‐E36 had a switch in macrophage cytokine profile towards an anti‐inflammatory phenotype 67. When NOX‐E36 was given for 3 months in a randomised double‐blind placebo controlled Phase IIa clinical trial, a 29% reduction in ACR was observed with no change to GFR 68…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%
See 2 more Smart Citations